2005
DOI: 10.1007/s10584-005-5384-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variability and Land-use Change in Danangou Watershed, China—Examples of Small-Scale Farmers' Adaptation

Abstract: With global concern on climate change impacts, developing countries are given special attention due their susceptibility. In this paper, change and variability in climate, land use and farmers' perception, adaptation and response to change are examined in Danangou watershed in the Chinese Loess Plateau. The first focus is to look at how climate data recorded at meteorological stations recently have evolved, and how farmers perceived these changes. Further, we want to see how the farmers respond and adapt to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 32 publications
5
53
0
2
Order By: Relevance
“…is very impressive as they interact directly with the nature. Similar observations have also been found by Mahmood et al [7], Anik and Khan [9], Chaudhary and Bawa [16], Byg and Salick [45], Mertz et al [46] and Apata [47], all of which indicate that climate is changing, while some other studies, such as Chaudhary and Bawa [16], Chaudhary et al [17], Hageback et al [48], Cabrera et al [49], Thomas et al [50] and Shrestha et al [51] have validated community perception with scientific evidence. Interestingly, indigenous people from tropical forest areas have reported that natural signals that were used to trigger activities in the past are now less reliable as the weather becomes hotter and the rainy season comes earlier or later than usual, which can lead to a disorientation of people in their daily lives [52].…”
Section: Discussionsupporting
confidence: 85%
“…is very impressive as they interact directly with the nature. Similar observations have also been found by Mahmood et al [7], Anik and Khan [9], Chaudhary and Bawa [16], Byg and Salick [45], Mertz et al [46] and Apata [47], all of which indicate that climate is changing, while some other studies, such as Chaudhary and Bawa [16], Chaudhary et al [17], Hageback et al [48], Cabrera et al [49], Thomas et al [50] and Shrestha et al [51] have validated community perception with scientific evidence. Interestingly, indigenous people from tropical forest areas have reported that natural signals that were used to trigger activities in the past are now less reliable as the weather becomes hotter and the rainy season comes earlier or later than usual, which can lead to a disorientation of people in their daily lives [52].…”
Section: Discussionsupporting
confidence: 85%
“…2). Small-scale farmers studied in China by Hageback et al (2005) showed considerable potential adaptation to climate change, including the diversification of livelihoods. Bates (2002) found that another common response is out-migration by people from areas under environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Local knowledge is based on practice and assists farmers to make informed decisions about how to respond to environmental changes and how to improve the amount and quality of their yield [13,[32][33][34][35][36][37][38]. The validity of local knowledge has been shown by scientists through comparison with quantitative climate data analysis [39][40][41][42]. The majority of studies show that farmers' resourcefulness matches quantitative data analysis: local knowledge is used to respond to the vagaries of climate such as droughts, famines, floods and other stresses that threaten crops and livestock [38,[39][40][41][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of local knowledge has been shown by scientists through comparison with quantitative climate data analysis [39][40][41][42]. The majority of studies show that farmers' resourcefulness matches quantitative data analysis: local knowledge is used to respond to the vagaries of climate such as droughts, famines, floods and other stresses that threaten crops and livestock [38,[39][40][41][43][44][45][46][47][48][49][50]. However, there have also been cases where local knowledge failed to match quantitative climate data, making local knowledge seem unreliable, e.g., as reported from Kenya by Rao et al [51].…”
Section: Introductionmentioning
confidence: 99%